Andrographolide prevents human nucleus pulposus cells against degeneration by inhibiting the NF‐κB pathway. Issue 6 (28th October 2018) - Liu, Jianwei; Jiang, Tongmeng; He, Mingwei; Fang, Depeng; Shen, Chong; Le, Yiguan; He, Maolin; Zhao, Jinmin; Zheng, Li
Abstract: Intervertebral disc degeneration (IDD) is among the most common spinal disorders, pathologically characterized by excessive cell apoptosis and production of proinflammatory factors. Pharmacological targeting of nucleus pulposus (NP) degeneration may hold promise in IDD therapy, but it is limited by adverse side effects and nonspecificity of drugs. In this study, we used a natural compound, andrographolide (ANDRO), which has been widely used to intervene inflammatory and apoptotic diseases in the investigation of NP degeneration based on IDD‐patients‐derived NP cells by lipopolysaccharide (LPS) treatment for the preservation of degeneration. The results showed that LPS maintained the degeneration status of NP cells as evidenced by a high apoptosis rate and the expression of degenerative and inflammatory mediators after LPS treatment. ANDRO reversed the effects of LPS‐caused degeneration of NP cells and maintained the phenotype of NP cells, as demonstrated by flow cytometry, degenerative mediators ( ADAMTS4 and ADAMTS5 ), inflammatory factors ( COX2, PGE2, MMP‐13, and MMP‐3 ), biomarkers of NP cells ( SOX9, ACAN, and COL2A1 ) expressions, and glycosaminoglycan secretion. We also found the involvement of the nuclear factor kappa‐light‐chain‐enhancer of the activated B cells (NF‐κB) pathway in ANDRO treatment, indicating that ANDRO prevented the LPS‐preserved degeneration of NP cells by inhibiting the NF‐κB pathway. This study may provide a reference for clinic medication of IDD therapy. Abstract : ANDRO has a potent effect on nucleus pulposus (NP) degeneration based on the in vitro model of intervertebral disc degeneration (IDD) patients‐derived NP cells by lipopolysaccharide (LPS) treatment to preserve degeneration, as evidenced by the prevention of cell apoptosis and inflammation. ANDRO reversed the NP degradation by blocking the nuclear factor kappa‐light‐chain‐enhancer of the activated B cells (NF‐κB) pathway.